1 & 2 Samuel - Jensen, David Hadley, 1968- (Belief (Series), 2015)
First and Second Samuel describe the beginnings of monarchy in ancient Israel and introduce us to intriguing characters: Samuel--prophet, priest, and judge; Saul--the tragic figure who becomes Israel's first king; and David--Saul's celebrated successor and Israel's key leader whose influence endured for generations. But as Jensen makes clear in his splendid commentary, there is another figure who is a central character: God. Throughout his theologically rich treatment of these biblical books, Jensen explores what makes these texts important for us. He suggests that we read 1 and 2 Samuel because they reveal the complexities of the human person; the ambiguities of our social arrangements as nations; and God's agency in a conflicted world. Jensen notes that as we are shaped by and grapple with the biblical stories, we are invited to find our own stories within them. "What keeps us coming back to faith," he says, "is its stories: stories that tell the truth about the human condition, our shared corporate life, and the life God gives to the world."